2010
DOI: 10.1080/19440049.2010.489578
|View full text |Cite
|
Sign up to set email alerts
|

Determination of furan in jarred baby food purchased from the Spanish market by headspace gas chromatography-mass spectrometry (HS-GC-MS)

Abstract: The aim of this paper is to offer a method based on headspace gas chromatography-mass (HS-GC-MS) spectrometry technique in-house validated and use to estimate furan concentrations in jarred baby-food samples purchased from the Spanish market. The validation was performed according to ISO 17025 and European Food Safety Authority (EFSA) requirements and the results obtained (limit of detection (LOD) = 0.05 microg kg(-1); limit of quantification (LOQ) = 4 microg kg(-1), lowest validated level; relative standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…The highest average content was found in the vegetable-based baby food group (63.0 + 37.2 mg/kg) ranging from 10.9 to 143.0 mg/kg, whereas the fruit-based baby food group presented the lowest average content (16.6 + 6.0 mg/kg) ranging from 7.7 to 32.1 mg/kg. These data agree with the findings of several authors (Jestoi et al, 2009;Lachenmeier et al, 2009;Ruiz, Santillana, Nieto, Cirugeda, & Sanchez, 2010;Zoller, Sager, & Reinhard, 2007), who have observed a higher furan content in vegetable-based baby food than in fruit-based samples. Moreover, the results are in accordance with the assumptions reported in a previous study by the present authors (Mesı´as-Garcı´a et al, 2010), in which it was concluded that the higher furan content of vegetable-based baby food may be associated with greater ascorbic acid degradation in the presence of oxygen, which is favored by a higher pH in these samples (pH ¼ 5.7) compared to fruitbased baby food (pH ¼ 3.9).…”
Section: Furan In the Baby Food Samplessupporting
confidence: 83%
“…The highest average content was found in the vegetable-based baby food group (63.0 + 37.2 mg/kg) ranging from 10.9 to 143.0 mg/kg, whereas the fruit-based baby food group presented the lowest average content (16.6 + 6.0 mg/kg) ranging from 7.7 to 32.1 mg/kg. These data agree with the findings of several authors (Jestoi et al, 2009;Lachenmeier et al, 2009;Ruiz, Santillana, Nieto, Cirugeda, & Sanchez, 2010;Zoller, Sager, & Reinhard, 2007), who have observed a higher furan content in vegetable-based baby food than in fruit-based samples. Moreover, the results are in accordance with the assumptions reported in a previous study by the present authors (Mesı´as-Garcı´a et al, 2010), in which it was concluded that the higher furan content of vegetable-based baby food may be associated with greater ascorbic acid degradation in the presence of oxygen, which is favored by a higher pH in these samples (pH ¼ 5.7) compared to fruitbased baby food (pH ¼ 3.9).…”
Section: Furan In the Baby Food Samplessupporting
confidence: 83%
“…Bianchi et al (2006) assumed that this difference in furan content could be due to different heating treatment as fruit samples are generally pasteurised whereas the vegetables are generally sterilised. Also in Brazil (Arisseto et al, 2010), in Spain (Ruiz et al, 2010) and in Finland (Jestoi et al, 2009) it was demonstrated that jarred baby food containing vegetables showed statistically significant higher mean furan values in comparison to those containing fruits only. In the present study, the 10-fold difference in mean furan content between the fruit-based baby food and vegetables only or in combination with meat was taken into account when assessing dietary exposure for infants and toddlers to furan.…”
Section: Infant Foodmentioning
confidence: 99%
“…Due to their volatility, analysis of furanic compounds is currently carried out by headspace (HS) sampling (Ruiz et al 2010) or headspace solid-phase micro-extraction (HS-SPME) (Altaki et al 2007;Jestoi et al 2009;Poinot et al 2007) both followed by GC/MS. However, determination of furfural has also been performed by methods such as RP-HPLC (Coco et al 1997), GC-FID (Takeoka et al 1996), GC-MS and SPME-GC-MS (Giordano et al 2003).…”
Section: Introductionmentioning
confidence: 99%